Notas sobre o currículo como prática de tradução cultural - RIBEIRO, Joyce Otânia Seixas (Universidade Federal do Pará, 2021)
The article is part of a doctoral thesis, and intends to discuss the cultural translation as a theoretical tool. To ful" ll this task, we will have a brief theoretical foray with the intention to get to the notion of cultural translation of Bhabha (1998). ! en we will trigger such a notion of translation in curriculum debate, with the intention of outlining the curriculum as a practice of cultural translation.